The Gallerist’s Gambit: Financial Innovation, Tax Law, and the Making of the Contemporary Art Market - Maizels, Michael W.; Foster, William E. (The Columbia Journal of Law & the Arts, 2019)
This essay presents an account of an important moment in the emergence of the market for Pop art that was facilitated in part by a distinctly accommodating legal environment. Although Abstract Expressionism is commonly credited with causing American art’s ascendance onto the world stage immediately after World War II, its international acclaim belied a precarious institutional and financial infrastructure for living American painters. It was only with the following generation of Pop and Minimalist artists that the United States developed a self-sustaining market for the work of contemporary American artists. A significant but largely overlooked factor in that continued success was the ability of art dealers to take advantage of the unique legal and regulatory environment of the 1960s. This essay focuses on the efforts of an enterprising art gallerist, Leo Castelli, to aggressively promote his stable of Pop artists through the development of several financial structures, including some designed to leverage the relatively generous income tax deductions and anemic enforcement regime of the time. In doing so, Castelli not only seeded the ground for the international ascendance of American visual art, but also engineered financial arrangements that fostered the development of a lucrative and resilient art market that endures to this day.